2012
DOI: 10.1103/physrevb.85.054203
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state characterizations of systems predicted to exhibitL11orL13crystal structures

Abstract: Despite their geometric simplicity, the crystal structures L11 (CuPt) and L13 (CdPt3) do not appear as ground states experimentally, except in Cu-Pt. We investigate the possibility that these phases are ground states in other binary intermetallic systems, but overlooked experimentally. Via the synergy between high throughput and cluster expansion computational methods, we conduct a thorough search for systems that may exhibit these phases and calculate order-disorder transition temperatures when they are predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…Fig. 1 shows the heats of formation ∆H for homogeneous solid solutions and imaginary intermetallics AgPd 3 (L1 2 or D0 22 ), AgPd (L1 0 or [64][65][66][67][68][69][70] It was theoretically suggested that stable intermetallics might exist at low temperature, in contrast to experimental phase diagram. For example, DFT calculations indicated that D0 23 , D0 24 , L1 2 (all for Ag 3 Pd), L1 1 (for AgPd), and L1 3 (for AgPd 3 ) are the possible ground states but may be overlooked experimentally as the low order-disorder transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1 shows the heats of formation ∆H for homogeneous solid solutions and imaginary intermetallics AgPd 3 (L1 2 or D0 22 ), AgPd (L1 0 or [64][65][66][67][68][69][70] It was theoretically suggested that stable intermetallics might exist at low temperature, in contrast to experimental phase diagram. For example, DFT calculations indicated that D0 23 , D0 24 , L1 2 (all for Ag 3 Pd), L1 1 (for AgPd), and L1 3 (for AgPd 3 ) are the possible ground states but may be overlooked experimentally as the low order-disorder transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has also been used to calculate the solubility of elements in titanium alloys [71], to study the effect of hydrogen on phase separation in iron-vanadium [72], and to find new superhard tungsten nitride compounds [73]. The data has been employed to generate structure maps for hcp metals [74], as well as to search for new stable compounds with the Pt 8 Ti phase [75], and with the L1 1 and L1 3 crystal structures [76]. Note that even if a structure does not lie on the ground state convex hull, this does not rule out its existence.…”
Section: Automated Computational Materials Design Frameworkmentioning
confidence: 99%
“…Based on the early work of Schneider and Esch [35] and subsequent refinements, the phase diagram of DF is surprising. It eliminates two of the intermediate compounds (at 45% and 75% platinum), and the 50%-Pt phase, computationallypredicted [3,27,38,33,28,4] in several works to be L1 1 (isostructural to Cu 1 Pt 1 ), is replaced by a compound at 53%. Based on x-ray diffraction (XRD) and EPMA data, the DF authors speculate that this compound has a concentration of 53%-Pt (atomic %), with a cubic cell with at least 32 atoms and a stoichiometry of 15:17.…”
Section: Introductionmentioning
confidence: 99%
“…Several computational studies predict [27,38,33,28,4] the L1 1 structure (isostructural to Cu 1 Pt 1 ), a 50%-Pt compound, in the middle of the phase diagram instead of DF's 53%-Pt structure. Since ab initio calculations are limited to T = 0 K predictions and the DF measurements were made at finite temperatures, one is left to wonder whether the discrepancy is genuine or merely due to finite temperature effects.…”
Section: Introductionmentioning
confidence: 99%